If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-2k + -2) + (7k + 5) = 0 Reorder the terms: 6(-2 + -2k) + (7k + 5) = 0 (-2 * 6 + -2k * 6) + (7k + 5) = 0 (-12 + -12k) + (7k + 5) = 0 Reorder the terms: -12 + -12k + (5 + 7k) = 0 Remove parenthesis around (5 + 7k) -12 + -12k + 5 + 7k = 0 Reorder the terms: -12 + 5 + -12k + 7k = 0 Combine like terms: -12 + 5 = -7 -7 + -12k + 7k = 0 Combine like terms: -12k + 7k = -5k -7 + -5k = 0 Solving -7 + -5k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -5k = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -5k = 0 + 7 -5k = 0 + 7 Combine like terms: 0 + 7 = 7 -5k = 7 Divide each side by '-5'. k = -1.4 Simplifying k = -1.4
| 8x^4+12x^3-20x^2=0 | | 3x^2-14=5 | | [(4k-3)/(k-3)=]^1/20 | | 72.3456=3.14*r*r | | 4x+14y=20 | | 2.(15/Y)-4y=-14 | | 8y+2*60= | | 6x+12=90 | | 300=2l+2w | | 6x+139=4x+119 | | 10x-3=8x17 | | X^3-8x-36=0 | | (4k-3)/(k-3)=0 | | x(2)+5=-13 | | 2m-7=5m | | 4x+7=7x+-3 | | E=1l+2.25h | | 17=7w-4 | | 49=7(n+6) | | 9x+3=3x-4 | | 4688x+787878y=0 | | 2x^20-8x^10+x-2=0 | | 4(-12k-6)=8(-k+2) | | 2(5x+3)=4x+10+6x-4 | | (9x-40)=(5x+8) | | 6x-5=-3x+13 | | x+x+10=550 | | 65x+50y=63 | | 3x^2(x-3)+7x(x-3)-20(x-3)=0 | | p=300-2w-2l | | -7x+3=10 | | -8=33-5q |